Teachers’ Perspectives on Integrating Home and School-Based Learning in Primary Education: A Qualitative Study - Fatima Rauf; Dr. Hajra Bibi; Dr. Farkhanda Jabeen; Dr. Um-e-Rubab (Indus Journal of Social Sciences, 2025)
This research study was design to understand teachers’ opinions regarding the home versus school education differences in primary student development while identifying possible learning challenges that home-schooled students face compared to their classmates in regular classrooms. It was a Phenomenology study to dig out the teachers’ perspective regarding their experience with homeschooled children in term their social adjustment, academic performance and overall development in comparison to children enrolled in traditional schools. The research design conformed to qualitative methods through conducting interviews with fifteen primary-grade teachers in five schools. The analysis showed that an integrated educational approach improves student grades simultaneously with enhancing students’ interaction and pushing better participation from parents. The respondents identified problems which include disparity in resource availability and parent-school communication irregularities. Teachers shared that homeschooled children are more studious, independent and responsible however their social skills are weak. Students with traditional education system are more active in co-curricular activities and more enjoy group work. Teachers’ views show that there is no huge gap between both of these children however homeschooled children face issues in adjustment initially they require individual attention from the teachers but gradually they adopt the situation on their individual pace. The research ends with the findings that homeschooling creates individualized educational experiences and promotes independent thinking but faces difficulties with social engagement and diverse learning content demands coordinated actions between teachers and monetary bodies and guardians to support students’ equal academic and social development between all educational contexts.